2015
DOI: 10.5430/jbei.v1n1p11
|View full text |Cite
|
Sign up to set email alerts
|

An integrated system for the complete segmentation of the common carotid artery bifurcation in ultrasound images

Abstract: The complete segmentation of the common carotid artery (CCA) bifurcation in ultrasound images is important for the evaluation of atherosclerosis disease and the quantification of the risk of stroke. The current research work further evaluates and validates a semi-automated (SA) snake's based segmentation system suitable for the complete segmentation of the CCA bifurcation in two-dimensional (2D) ultrasound images. The proposed system semi-automatically estimates the intima-media thickness (IMT), the atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…However, we have found that some authors pointed out the need for automated measurement of carotid lumen diameter [47][48][49]. The lumen segmentation algorithms have been classified into regional-based vs. boundary-based: region-based [17,18], boundary-based [19][20][21][22]. Here, we describe each of these techniques and their limitations and discuss how they validated the measured parameters.…”
Section: Brief Survey and Benchmarkingmentioning
confidence: 96%
See 2 more Smart Citations
“…However, we have found that some authors pointed out the need for automated measurement of carotid lumen diameter [47][48][49]. The lumen segmentation algorithms have been classified into regional-based vs. boundary-based: region-based [17,18], boundary-based [19][20][21][22]. Here, we describe each of these techniques and their limitations and discuss how they validated the measured parameters.…”
Section: Brief Survey and Benchmarkingmentioning
confidence: 96%
“…The study by Loizou et al [20] was concentrated on bifurcation region segmentation and diameter estimation through speckle reduction filtering and snake-based segmentation. This algorithm faced the challenge of initialization of snakes and did not give a high value of coefficient of correlation between their method and manual reading (CC = 0.63).…”
Section: Brief Survey and Benchmarkingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in [37], there are no LD error statistics, only an overlap index of 79%. In [42], the LD error is under 100 m on average, but there is no data about statistical dispersion (see Table 6).…”
Section: Manual Vs Automatic Ld Measurementsmentioning
confidence: 97%
“…These proposals implement two stages, one to initialize the contours and a second one to segment the artery walls. Following the same idea, other authors have proposed methods based on models [36] or different implementations of active contours [37,38], like active contours without edges [39] based on the Chan-Vese snake [40], or frequency-formulation of active contours [41]. The latter, needs to perform twice the active contour segmentation,increasing the computational cost, and this work lacks the comparison of the results with a ground truth segmentation.…”
Section: Introductionmentioning
confidence: 94%